Une financiarisation si discrète ? La circulation des standards de la filière d’investissement en immobilier tertiaire dans les politiques de développement urbain du Grand Lyon - Antoine Guironnet (Métropoles)
In France, the concept of financialisation has stayed at the edges of urban studies. This situation is paradoxical given the rise of financial investors and the spread of market finance-based techniques in multifarious parts of the built environment (infrastructures, commercial property) in the 1990s, and the contribution of these sectors to urban redevelopment. Against this background, the article argues for accounts cognisant of the actors from the commercial property investment industry (financial investors, developers, brokers), whose business corresponds to the production of “quasi-financial assets”, in order to analyse urban development projects and policies. The Lyon city-region is thus reexamined through a case-study of the Carré de Soie large-scale regeneration project and the Schéma d’Accueil des Entreprises, both undertaken by the metropolitan authority (Grand Lyon). Its recent property-led economic policy has contributed to further the circulation of financial investors’ expectations, which are not only preempted by property developers. The metropolitan authority has also gradually integrated them as its economic development staff has became more acquainted with the regional actors of the industry. Yet these selective expectations bear upon urban redevelopment through the location and standardisation of commercial properties, and the selection of their tenants. In conclusion the article discusses the concept of financialisation by sketching an urban political economy approach to study the restructuring of power relationships between city governments and financial investors based on their rise in the urban built environment.